Pengaruh Service Quality Terhadap Repurchase Intention Melalui Customer Satisfaction Pada Q-Life Klinik Surabaya - Roos Indah Kamal. W. Taher; Fadhliah M. Alhadar; Ida Hidayanti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of service quality on repurchase intention through customer satisfaction at Q-life Clinic Surabaya. The number of samples in this study were 150 respondents. The data analysis technique used path analysis, using the PLS (Partial Least Squares) program. The results of this study indicate that: (1) Service Quality has a positive and significant effect on Repurchase Intention. (2) Service Quality has a positive and significant effect on Customer Satisfaction at Q-life Surabaya clinic. (3) Customer Satisfaction has a positive and significant effect on Repurchase Intention at Q-life Surabaya clinic. (4) Service Quality has a positive and significant effect on Repurchase Intention through Customer Satisfaction at the Q-life clinic in Surabaya.